Electrobioremediation of oil spills. (1st May 2017) - Daghio, Matteo; Aulenta, Federico; Vaiopoulou, Eleni; Franzetti, Andrea; Arends, Jan B.A.; Sherry, Angela; Suárez-Suárez, Ana; Head, Ian M.; Bestetti, Giuseppina; Rabaey, Korneel
Abstract: Annually, thousands of oil spills occur across the globe. As a result, petroleum substances and petrochemical compounds are widespread contaminants causing concern due to their toxicity and recalcitrance. Many remediation strategies have been developed using both physicochemical and biological approaches. Biological strategies are most benign, aiming to enhance microbial metabolic activities by supplying limiting inorganic nutrients, electron acceptors or donors, thus stimulating oxidation or reduction of contaminants. A key issue is controlling the supply of electron donors/acceptors. Bioelectrochemical systems (BES) have emerged, in which an electrical current serves as either electron donor or acceptor for oil spill bioremediation. BES are highly controllable and can possibly also serve as biosensors for real time monitoring of the degradation process. Despite being promising, multiple aspects need to be considered to make BES suitable for field applications including system design, electrode materials, operational parameters, mode of action and radius of influence. The microbiological processes, involved in bioelectrochemical contaminant degradation, are currently not fully understood, particularly in relation to electron transfer mechanisms. Especially in sulfate rich environments, the sulfur cycle appears pivotal during hydrocarbon oxidation. This review provides a comprehensive analysis of the research on bioelectrochemical remediation of oil spills and of the key parameters involved in the process. Graphical abstract: Highlights: Electrobioremediation is an innovative approach for contaminants removal. Oil spills can be successfully removed by electrobioremediation. Several parameters (e.g. electrode, potential, mediators) influence the process. Microbiological processes can be complex and sulfur cycle has an important role. The scale-up of the technology is the future challenge.